Project Management through the lens of Artificial Intelligence - Butt, Annaam (My University, 2018)
“Artificial intelligence has had much the same effect as Darwin's theory. Both aroused in some people anxieties about their own uniqueness, value and worth.” ― Herbert A. Simon Herbert A. Simon painted a very real picture of the perception regarding artificial intelligence systems in the world. Despite wide recognition of the potential benefits of using these systems to improve human lives today, the uncertainty related to new technology as well as the lack of systematic knowledge related to the potential of AI systems has led to a slow progress of development in this regard. Project management as a function is going through a revolutionary phase of change brought on by the digital era. This, among other factors, has prompted project managers to look towards finding new and creative ways to work better and more efficiently through the use of technology. Artificial intelligence for project management is a specific area of focus that has so far not been looked into and remains largely unexplored, especially in light of the upcoming digital era. This study is a pioneer in this regard and is an exploratory investigation into how artificial intelligence systems can be used to support project managers with becoming more efficient in their daily work. In order to achieve a preliminary understanding, an online survey first was conducted amongst project managers. The results of the survey were used to supplement the second step in the research process which consisted of semi-structured interviews with project managers to gain an in-depth understanding of the topic as well as to find areas of opportunities which can be used for future research and developments. The research proved quite fruitful in understanding and establishing the needs of the project managers who were involved directly in this investigation as key stakeholders. The study has also been successful in establishing a foundation for AI scientists to use for the purpose of developing tailored solutions for project managers.
Keywords: Innovation och entreprenörskap (nyttiggörande); Övrig annan teknik; Innovation & Entrepreneurship; Other Engineering and Technologies not elsewhere specified